2010
DOI: 10.4314/gjass.v8i2.51893
|View full text |Cite
|
Sign up to set email alerts
|

Profitability analysis and management practices among poultry farmers in Yola metropolis of Adamawa state, Nigeria

Abstract: This study analysis the profitability and management practices among poultry farmers in Yola metropolis of Adamawa State, Nigeria. The objectives of the Study were to: identify and describe the socio-economic characteristics of Poultry farmers in Yola metropolis, determine the costs of inputs and output returns, determine the resource use efficiency and to identify the major constraints of poultry farmers in the study area. Data were obtained from 75 purposively selected poultry farmers. The result of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The birds were given water which usually sourced from boreholes as indicated by majority (66%) of the farmers. Jongur, Oji, Yahaya and Tashikalma (2009) in their study on profitability analysis and management practices among poultry farmers in Yola metropolis of Adamawa state, Nigeria showed that poultry production is profitable in the area due to good management practices. The result from table 5 reveals that farmers obtained their stock by direct purchase as reported by (92%) of them and usually sourced income from different ways.…”
Section: Management Practices In Turkey and Guinea Fowl Productionmentioning
confidence: 99%
“…The birds were given water which usually sourced from boreholes as indicated by majority (66%) of the farmers. Jongur, Oji, Yahaya and Tashikalma (2009) in their study on profitability analysis and management practices among poultry farmers in Yola metropolis of Adamawa state, Nigeria showed that poultry production is profitable in the area due to good management practices. The result from table 5 reveals that farmers obtained their stock by direct purchase as reported by (92%) of them and usually sourced income from different ways.…”
Section: Management Practices In Turkey and Guinea Fowl Productionmentioning
confidence: 99%
“…The poultry industry has become the fastestexpanding and the most dynamic segment in the livestock sector (Emokaro and Eweka, 2015). After Nigeria independent in 1960, poultry production has grown from rearing a few birds in the backyard for family consumption to a thriving industry (Jongur et al, 2009). Poultry has been merely kept to obtain some money, also as a means of knowing when daytime is near and in some communities; it has been kept for the game of Cockfighting.…”
Section: Introductionmentioning
confidence: 99%
“…The inability of farmers to access information varies with locations in Nigeria. Adamawa State has a very high potential of becoming a leading producer of poultry products in the Northeast region with over 8.3 million poultry birds (Adene and Oguntade, 2006;Jongur et al, 2009;FAO and ICRISAT, 2019). The State's climatic condition, location, population, and socio-economic status of the people when properly exploited can increase the fortunes of the state in the venture.…”
Section: Introductionmentioning
confidence: 99%